Chinese cross‐border mergers and acquisitions in the developing world: Is Africa unique? - Gunessee, Saileshsingh; Hu, Shuang (Wiley-Liss Inc., 2020)
China has emerged as an important partner for Africa. Not surprisingly, Chinese business and investment relations with Africa have been growing. This article contends that Africa offers a different proposition to Chinese business interests in non-African developing economies. In this optic, it takes a “comparative” institution-based view treating factors that determine Chinese multinationals' cross-border merger and acquisition (CBMA) decisions as comparatively different for Africa to the rest of the developing world. From a panel data estimation of the number of Chinese CBMAs from 2007 to 2016, we find among market size, natural resources, strategic assets, labor productivity, and institutional governance, only natural resources and market size have a distinctive effect, with Chinese investors being more attracted to African natural resources than the African market. The drive for natural resources provides impetus for Chinese MNEs to choose CBMAs over greenfield investment, and through majority ownership to exercise control. Our inference is that Africa is “significantly” different from other developing regions, in terms of CBMAs, as Chinese multinationals have a strong motive to control access to natural resources.